ANALISIS KINERJA PEGAWAI DI BADAN KEPEGAWAIAN DAERAH (BKD) KABUPATEN CILACAP - Setyaningrum, Diana Ayu; Rihandoyo, Rihandoyo (Journal of Public Policy and Management Review, 2016)
The purpose of this research is to analyze employee performance at the employee department of Cilacap regency. In analyzing the performance of employees, researcher use the employee performance assessment indicators and factors that may affect employee performance. This type of research is descriptive qualitative, then data collection through interviews, documentation and observation. The informant are the secretary, the head of the field and employees of the employee department of Cilacap regency. From the research results show that the employee performance of the employee department of Cilacap regency is not optimal, because still there are problems. Based on the quantity indicators, showed that there are still a target that has not been done and the work that exceeded the target thereby increasing the workload. In terms of quality, found many mistakes made in carrying out the work because of the less of acuracy and understanding. Based of the work time, it was discovered there are many employees who do not use work hours to be effective. Factors that influence employee performance used researcher from Wirawan theory. Internal employee factors indicate that personal problem can obstruct the performance. Based of the internal environmental organization factors, there are still some problems that less facilities and there are distruption from trader coming into the room office. Based on the existing problems, there are some recomendations that can do that is to increase the amount of human resources, need to improve monitoring and evaluation, give the punishment for employees who violate the provisions and give reward system for employees who perform superior, need for development staff program routine, it is necessary to use finger print for attendance, need to complementary of office facilities and routine maintenance of the facilities and infrastructure.